LAYANAN E-COMMERCE PENJUALAN PAKAIAN BERBASIS WEB DENGAN PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT - Tudenga, Heldi Diana; Malelak, Yohanis (Universitas Boyolali, 2018)
badi Collection Shop is a business entity engaged in the sale of clothing located on the roadRoundabout PU Tuak Daun Merah II. In conducting its business processes the Abadi Collection Shopstill uses the conventional mechanism, the customer must come directly to the outlet to see and searchfor products sold by Abadi Collection Shop. In order to support the business run by Abadi CollectionShop, the existence of customers is not only a source of company income but also as a long term assetthat needs to be managed and maintained through Customer Relationship Management. The purposeof this research is to design and build an Application Service E-commerce Web Based Clothing Salesby applying Customer Relationship Management at Abadi Collection Shop. Data collecting method bywriter is literature study, observation and interview, tool of analysis of system design in the form ofdocument flow, context diagram, data flow diagram, and proposed database of entity relationshipdiagram. While making the software in this thesis, the writer uses PHP and Adobe Dreamwaver CS6and MySQL database. The results of this study system designed to support order transactions as wellas a promotional event that can facilitate customers in communication and provide input for AbadiCollection Shop.